The effect of Matricaria chamomile on menstrual related mood disorders - Elham Najafi Mollabashi; Tahereh Ziaie; Zahra Bostani Khalesi (Elsevier, 2021)
Objective: A significant percentage of reproductive-age women experience mood symptoms during the days before menstruation that can affect different aspects of a person's life, the use of some medicinal plants can be helpful in controlling premenstrual emotional symptoms. The aim of this study was to evaluate the effect of chamomile capsules on menstrual-related mood disorders. Study design: This clinical trial study was performed on 118 students of Guilan University of Medical Sciences. Participants were divided into two groups of chamomile and placebo. Both groups received one capsule every 8 h for 7 days before the onset of menstrual bleeding. The data collection tool was a Premenstrual Symptoms Screening Tool (PSST). Data analysis was performed using Mann-Whitney, independent t-test, Wilcoxon, and analysis of covariance. Results: According to the results of the Mann-Whitney test Chamomile capsules were more effective than placebo in reducing menstrual-related mood disorders (p < 0/001). The results of the analysis of covariance showed that after controlling the associated variables, the changes in the severity of mood symptoms between the two groups were significantly different (p < 0/05). Conclusion: The results of this study show that the use of chamomile capsules can be an effective treatment in alleviating emotional symptoms related to menstrual cycles.